PEDAGOGICAL SUPPORT AS A MEANS REGULATION OF GENERAL EDUCATIONAL ENVIRONMENTS IN MODERN SCHOOL PRACTICE - N.I. Zelenkova; L.V. Hryhorenko (Academy of Cognitive and Natural Sciences, 2004)
The article is an orientation on a modern adjustment of general education surrounds in the practice of contemporary school.